Au-delà de l'expression « Le privé est politique » : de jeunes mères-activistes chicanas et la lutte pour un intérêt commun - Leah S. Stauber (Sociétés et Jeunesses en Difficulté)
While motherhood has sometimes inspired and guided women’s collective movements, particularly around children’s education and civil rights, the social and material pressures of mothering – including strains on time, budgets, and mobility – have more often circumscribed women’s participation in broader social movements, particularly those not oriented specifically toward children’s rights. Early childbearing and young motherhood, meanwhile, have been well-documented in the scholarly literature as delimiting young women’s social opportunities and civic participation. Yet in the southwestern U.S. city of Tucson, Arizona – a site quickly moving to the forefront of today’s battles over Mexican American rights and representation in the United States – a small and powerful contingent of “mother-activists” are charting new courses of collective self-determination, civic action, and social activism. This article, which derives from ethnography conducted across ten years, reveals the uniquely powerful form of mother-activist organizing and action that has characterized one vanguard of a broadly visible twenty-first century movement on the U.S.-Mexico border.